Experimental and theoretical studies of oxycarbenes: Their rearrangements, homolysis and intermolecular reactions with carbon disulfide - Reid, Darren L. (My University, 2000)
The first portion of this research focuses on some of the intramolecular chemistry of oxy- and dioxycarbenes. Carbenes belonging to this group are known to fragment to radicals, both in gas and in solution phases. The computational work presented here identifies the homolysis from the singlet ground state as a viable pathway for this fragmentation. The study then concentrates on the mechanism for the homolysis of these singlet carbenes and the possibility that this apparently-simple fragmentation could involve a transition state. In accordance with models, such as Valence Bond Configuration Mixing (VBCM), transition states involving changes in bonding are said to result from destabilization due to the change from one stable ground state electronic configuration to another. The results indicated that the homolysis has an unusual conformational dependence that cannot be explained by a first approximation of the VBCM model, and is in fact attributable to a mismatch in the electronic structures of the states involved. The second portion of this work focuses on expanding the chemistry of dioxycarbenes with thiocarbonyl compounds. To this end the reaction of dimethoxycarbene with carbon disulfide (CS2 ) is examined both experimentally and computationally. The reaction gave a surprisingly complicated product, which suggested the participation of zwitterionic, dipolar and neutral intermediates. The neutral thiocarbonyl intermediates are apparently quite reactive and undergo subsequent nucleophilic attacks by dimethoxycarbene. Initial results for the reaction of diphenoxycarbene with carbon disulfide showed diphenyl thionocarbonate as the only CS2 -derived product, emphasizing the influence that exchangeable carbene substituents have on the chemistry of the zwitterionic intermediates. Dihydroxycarbene was used to model the interactions of dioxycarbenes with CS2 . The theoretical results indicate that dioxycarbenes do not undergo concerted cycloadditions to a carbon-sulfur double bond, but instead prefer nucleophilic attack at carbon to form zwitterionic intermediates, or electrophilic attack at sulfur to form ylides with an unexpected twisted geometry. Direct nucleophilic attack at carbon has also been observed computationally by previous workers for the reaction of dihydroxycarbene with carbon dioxide. These results emphasize the differences between cumulated systems and simple carbonyl systems studied in the past. Both the zwitterionic and ylide intermediates have available reaction pathways to thionocarboxylic acid (HOCSOH) and carbon monosulfide, however it was not possible to distinguish a preferred route from these results.
Keywords: Chemistry; Chemistry